Epidemiological study of burns registered in Fatemi hospital in Ardabil, 2016 - Zakeri, Anahita; Amani, Firouz; Abbasi, Vahid (International Journal of Research in Medical Sciences, 2018)
Background: Burns after traffic accidents, falls and interpersonal violence are the fourth most commonly damaged worldwide. Annually more than 11 million people suffered to sever burns that most of them need for interventions and according WHO statistics, yearly more than 300000 people die from fire-related burns and most of them occurred in low income countries. The aim of this study was Epidemiological study of burns registered in Fatemi hospital in Ardabil, 2016. Methods: This cross-sectional descriptive study has been done on 200 burns registered in burn unit of Fatemi hospital in 2016. Information included age, sex, residence place (urban-rural), marital status, time and area of burn, percent and degree of burn, cause and mechanism of burn, hospitalized time and result of treatment completed by a checklist and analyzed by statistical methods in SPSS version 19. Results: Of all patients, 118 (59%) were male, 62.5% rural and 50% single. Most of burns occurred in age group less than 10 with 33%. The most common cause of burns was hot liquids with 51.5%. Most of cases had burn in degree 2 (71%) and 53.5% of cases hospitalized five days in hospital. 93.5% of patients improved and discharged. Conclusions: Results showed that most of burns in this study occurred in age group less than 10 year. So, that it is necessary to prevent these events in future by taking the necessary measures and control and prevention by families.